Non-curative surgery for patients with gastric cancer with local peritoneal metastasis: A retrospective cohort study. Issue 49 (December 2016) - Dong, Yuanqiang; Ma, Shulan; Yang, Shuo; Luo, Fen; Wang, Zhiming; Guo, Fenghua
Abstract : Abstract: The role of non-curative surgery for patients with M1 gastric cancer (GC) is controversial. This study aimed to evaluate the efficacy of non-curative resectional surgery for patients with GC with local peritoneal metastasis. We reviewed the medical records of 47 patients with GC with local peritoneal metastasis, which was found by laparotomy or laparoscopy. The patients were divided into 2 groups: those who underwent gastric resection (n = 29), and a non-resection group who did not (n = 18). The clinical characteristics, postoperative complications, mortality, palliative intervention, and long-term outcomes of the 2 groups were compared. Complications occurred more frequently in the resection group than in non-resection group ( P = 0.017). There was no postoperative mortality or reoperation in either group. Palliative intervention was performed in 9 (31%) patients in resection group and 16 (88.9%) patients in non-resection group ( P  < 0.001). The intervention interval and hospital-free time were significant longer in resection group than in non-resection group ( P  < 0.001, P  < 0.001). The Kaplan–Meier survival curves revealed that resection group had longer survival than non-resection group ( P  < 0.001). Non-curative resectional surgery helps prolong survival time and improve the quality of life for patients with GC with local peritoneal metastasis.